Pengembangan Media Pembelajaran POBISISTAR (Pop Up Book IPA Sistem Tata Surya) Untuk Peserta Didik Kelas VI Sekolah Dasar - Cahyati, Cahyati; Sari, Fita Permata; Budhiman, Arief (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The material about the solar system contains abstract ideas and cannot be witnessed directly; therefore, observation is needed to understand the processes that occur in the cosmos. The purpose of this study was to determine the feasibility and process of creating POBISISTAR (Solar System Pop-Up Science Book) teaching materials for sixth-grade elementary school students. The R&D approach created by Brog and Gall, which consists of the following stages: introduction, product design, product validation, and product trial, was used in this work. Data collection methods included student response questionnaires and questionnaire validation from media experts and material experts. The research findings showed that, according to validation from media experts and material experts, the POBISISTAR (Solar System Pop-Up Science Book) teaching materials for sixth-grade elementary school students were 80% and 78.67%, respectively. Ninety-five percent of students answered the questionnaire. According to the research findings, sixth-grade elementary school students can use POBISISTAR (Solar System Pop-Up Science Book) teaching resources. Materi tentang tata surya mengandung gagasan yang abstrak dan tidak dapat disaksikan secara langsung; oleh karena itu, pengamatan diperlukan untuk memahami proses yang terjadi di kosmos. Tujuan penelitian ini adalah untuk memastikan kelayakan dan proses pembuatan bahan ajar POBISISTAR (Pop Up Book IPA SistemTata Surya) untuk siswa kelas enam sekolah dasar. Pendekatan R&D yang dibuat oleh Brog dan Gall, yang terdiri dari tahapan-tahapan berikut: pendahuluan, desain produk, validasi produk, dan uji coba produk, digunakan dalam karya ini. Metode pengumpulan data meliputi angket respons siswa dan validasi angket dari ahli media dan ahli materi. Temuan penelitian menunjukkan bahwa, menurut validasi dari ahli media dan ahli materi, bahan ajar POBISISTAR (Pop Up Book IPA SistemTata Surya) untuk siswa kelas enam sekolah dasar masing-masing adalah 80% dan 78,67%. Sembilan puluh lima persen siswa menjawab angket. Menurut temuan penelitian, siswa kelas VI sekolah dasar dapat menggunakan sumber ajar POBISISTAR (Pop Up Book IPA SistemTata Surya).